CYSTIC HYGROMA-AN UNUSUAL CAUSE OF INDUCED ABORTION - Amin, Umar; Khan, Asad; Ghafoor, Trariq (Journal of Ayub Medical College Abbottabad, 2007)
A male infant was diagnosed prenatally at 20 weeks of gestation with posterior cervical cystic hygroma. The mother was a 31-year-old gravida , who had an otherwise normal systemic examination. A therapeutic abortion was arranged and fetus was aborted. Sonographic findings were confirmed on examination of aborted fetus Keywords: Ultrasound, Cystic, Septum